Effects of temperature on the growth, total lipid content and fatty acid composition of Skeletonema dohrnii - Shang, Xiaomei; Yang, Yaning; Zan, Yongling; Sun, Zhenwei; Lu, Zhengyi; Sun, Jun (Frontiers in Marine Science, 2024)
The potential of diatoms as aquatic bait, attribute to their abundance in highly unsaturated fatty acids, has been extensively studied. Temperature plays a crucial role in the synthesis of these fatty acids. This study specifically investigated the impact of temperature on the growth, total lipid content, and fatty acid composition of Skeletonema dohrnii, a planktonic diatom commonly associated with red tides and water blooms in China. The aim is to evaluate its suitability as an aquatic bait and provide insights for large-scale factory farming. Results indicated that the highest biomass and maximum growth rate occurred at 28°C, with no significant deviation from the control group at 25°C. At 28°C and 15°C, there was a significant increase in the total lipid content and the total fatty acid content, with a more pronounced effect at 15°C. At 28°C, EPA and DHA content measured at 0.97 ± 0.01 mg.DW.L-1 and 0.264 ± 0.01 mg.DW.L-1 respectively, surpass those at 15°C due to lower biomass. Conversely, at 15°C, substantial synthesis of long-chain polyunsaturated fatty acids, with EPA constituting up to 32.24 ± 0.24% of the total fatty acids, is observed. Modulating the temperature could optimize the utilization of S. dohrnii as an aquatic feed source. These findings underscore the potential of S. dohrnii as a high-quality aquafeed and lay the groundwork for its success in ocean warming scenarios.